2018
DOI: 10.1021/acs.organomet.8b00604
|View full text |Cite
|
Sign up to set email alerts
|

Newly Synthesized Heteronuclear Ruthenium(II)/Ferrocene Complexes Suppress the Growth of Mammary Carcinoma in 4T1-Treated BALB/c Mice by Promoting Activation of Antitumor Immunity

Abstract: The two new heterometallic Ru­(II)-tpy/ferrocene complexes [Ru­(tpy)­Cl2(mtefc)] (1) and [Ru­(tpy)­Cl2(mtpfc)] (2) (where tpy = 2,2′:6′,2′′-terpyridine, mtefc = (2-(methylthio)­ethyl)­ferrocene, and mtpfc = (3-(methylthio)­propyl)­ferrocene) have been synthesized and then characterized through elemental analysis, followed by various spectroscopic (IR, UV–vis, 1D and 2D NMR) and mass spectrometric techniques (MALDI TOF and ESI Q-TOF MS). UV–vis and fluorescence spectroscopy and viscometry were employed to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 80 publications
2
11
0
1
Order By: Relevance
“…[44] Milutinovic et al reported an intercalative binding of Ru/Fe heterobinuclear complexes bound with CT-DNA with binding constant K b = (5.2-7.2) × 10 3 . [45] By comparing the binding constant values (Table 3) with other reported ruthenium complexes, [44,45] we confirmed the intercalative binding nature of our Ru(III)/Fe(II) complexes. The intrinsic binding constants K b of the ligands and complexes for binding with CT-DNA were determined using the equation [46] :…”
Section: Dna Binding Studiessupporting
confidence: 81%
“…[44] Milutinovic et al reported an intercalative binding of Ru/Fe heterobinuclear complexes bound with CT-DNA with binding constant K b = (5.2-7.2) × 10 3 . [45] By comparing the binding constant values (Table 3) with other reported ruthenium complexes, [44,45] we confirmed the intercalative binding nature of our Ru(III)/Fe(II) complexes. The intrinsic binding constants K b of the ligands and complexes for binding with CT-DNA were determined using the equation [46] :…”
Section: Dna Binding Studiessupporting
confidence: 81%
“…Afterwards, characterization of the anticancer activity and toxicity in vivo of compounds that showed promising results in vitro, is fundamental to their further development (64). A number of in vivo studies have discovered that Ru(II) complexes exhibited anti-cancer activities comparable to, or even better than cisplatin, but with significantly less toxicity and side effects than cisplatin (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). Weiss et al synthesized ruthenium complex, [Ru(h 6 -pcymene)Cl 2 (pta)], where pta = 1,3,5-triaza-7-phosphaadaman tane (RAPTA-C).…”
Section: Ru(ii) Complexes Which Entered Preclinical and Clinical Trialsmentioning
confidence: 99%
“…Other ruthenium complexes also exhibited similar effects in vivo; all of them inhibited growth of tumor tissue and produced less systemic toxicity in comparison to cisplatin in vivo(71)(72)(73)(74)(75). It is worth noting that complexes synthesized by Milutinovic et al, Ru(II)tpy/ferrocene complexes [Ru(tpy) Cl 2 (mtefc)] and [Ru(tpy)Cl 2 (mtpfc)] (where tpy = 2,2′:6′,2′′-terpyridine, mtefc = (2-(methylthio)ethyl)ferrocene, and mtpfc = (3-(methylthio)propyl)ferrocene), promoted activation of acquired and innate antitumor immunity, which led to growth reduction of mammary carcinoma in vivo(76).…”
mentioning
confidence: 99%
“…Under this circumstance, transition metals such as ruthenium, iridium, and osmium are of interest due to their comparative lower toxicity, better selectivity, and novel mechanism for causing cell death. For example, these new mechanisms include DNA binding, inhibition of the activity of the proteins, or catalytic hydride transfer reactions in cells. Moreover, after the metal is complexed with π-conjugated auxiliary ligands such as arene, polypyridine, 1,10-phenanthroline, and their derivatives, with the modification of ligands, novel transition metal complexes can lead to a significant change in luminescence properties and anticancer efficacy. Among these transition metal complexes, Ru­(II) complexes were attractive due to their special photophysical properties and DNA binding mechanism for anticancer therapy .…”
Section: Introductionmentioning
confidence: 99%